2009
DOI: 10.1111/j.1523-5378.2009.00671.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis: Four‐Drug, Three‐Antibiotic, Non‐bismuth‐Containing “Concomitant Therapy” Versus Triple Therapy for Helicobacter pylori Eradication

Abstract: Background-Low success rates with triple therapy for Helicobacter pylori infections have prompted search for alternatives. In one a PPI and amoxicillin was followed by the PPI plus clarithromycin and a nitroimidazole (sequential therapy); in another these 4 drugs were given concomitantly (concomitant therapy).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
157
1
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 211 publications
(171 citation statements)
references
References 32 publications
(58 reference statements)
5
157
1
8
Order By: Relevance
“…Pooled estimates of the five RCTs showed superiority of non-bismuth-containing quadruple therapy over triple therapy with an OR of 2.86 (95 % CI 1.73-4.73) [36].…”
Section: Eradication Regimenmentioning
confidence: 98%
“…Pooled estimates of the five RCTs showed superiority of non-bismuth-containing quadruple therapy over triple therapy with an OR of 2.86 (95 % CI 1.73-4.73) [36].…”
Section: Eradication Regimenmentioning
confidence: 98%
“…Another meta-analysis showed that concomitant therapy was superior to STT [99] . In studies published in South Korea, the eradication rate for concomitant therapy was considerably higher than that for sequential therapy [100,101] .…”
Section: Are There Suitable Sequential and Concomitant Therapy Alternmentioning
confidence: 99%
“…The first quadruple non-bismuthcontaining regimen used these drugs concomitantly, typically twice a day. 9 Sequential therapy was a modification in which amoxicillin and a proton pump inhibitor were given for five days, followed by clarithromycin, a nitroimidazole and the proton pump inhibitor for five days (two drugs + three drugs). 10,11 In the presence of modest levels of clarithromycin resistance, these regi mens proved more successful than legacy triple therapy, generally providing between 90% and 94% eradication.…”
Section: Currently Recommended Regimensmentioning
confidence: 99%